ANALYSIS OF ANNUAL COMMODITY INCOME IN IMPROVING THE ECONOMY OF THE COMMUNITY IN MANMAS VILLAGE, ALOR REGENCY - Asadama, Salomo Aomanio Dafid; Olviana, Tomycho; Tungga, Cicilia Apriliana (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to examine the role of annual commodities, particularly coffee and candlenut, in improving the economy of the community in Manmas Village, Alor Regency. The research method used is a qualitative approach, with data collected through observation, interviews, and documentation studies involving coffee and candlenut farmers in Manmas Village. The sources of data include both primary and secondary data. The data analysis technique employed in this research is the interactive data analysis model by Miles and Huberman. The results of the study indicate that coffee and candlenut are leading commodities that contribute significantly to the income of the local community. The role of the government in maintaining price stability and providing protective policies is crucial to support the sustainability of community-based plantations. Overall, the development of annual commodities in Manmas Village has proven to enhance the community’s economic standard, although efforts are still needed to improve post-harvest quality, market access, and consistent policy support.